THE MIND CRITICISM IN POST-MODERN CONCEPSIONS - Грицай, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article presents the analysis of postmodern strategies of mind criticism which try to rehabilitate mind denying metaphysics, pluralization and decentralization of rationality.